Inequities in access to palliative and end-of-life care in the black population in Canada: a scoping review - Nahyeni Bassah; Julia Beranek; Megan Kennedy; Juliet Onabadejo; Anna Santos Salas (BMC, 2024)
Abstract Background Improving equity and early access to palliative care for underserved populations in Canada is a priority. Little is known regarding access to palliative and end-of-life care in the Black population. Methods We undertook a scoping review using the framework by Arksey and O'Malley to identify knowledge, access gaps, and experiences of palliative and end-of-life care among Blacks living with life-limiting illnesses in Canada. Primary studies, discussion papers, books, and reports were considered eligible. We followed a comprehensive search strategy developed by an information scientist. Searches were performed in the following bibliographic databases: Medline, EMBASE, PsycINFO via OVID, CINAHL via EBSCOhost, Scopus and Cochrane Library via Wiley. The search strategy was derived from three main concepts: (1) Black people; (2) Canada and Canadian provinces; (3) Palliative, hospice, or end-of-life care. No publication date or language limits were applied. Titles and abstracts were screened for eligibility by one reviewer and full text by two independent reviewers. Results The search yielded 233 articles. Nineteen articles were selected for full-text review, and 7 articles met the inclusion criteria. These studies were published between 2010 and 2021, and conducted in the provinces of Ontario and Nova Scotia only. Studies used both quantitative and qualitative methods and included cancer decedents, next of kin, family caregivers and religious leaders. Sample sizes in various studies ranged from 6 − 2,606 participants. Included studies reported a general lack of understanding about palliative and end-of-life care, positive and negative experiences, and limited access to palliative and end-of-life care for Blacks, across all care settings. Conclusion Findings suggest limited knowledge of palliative care and inequities in access to palliative and end-of-life care for Blacks living with life-limiting illnesses in 2 Canadian provinces. There is an urgent need for research to inform tailored and culturally acceptable strategies to improve understanding and access to palliative care and end-of-life care among Blacks in Canada.